The Impact of Fraud on the Detection of Fraud in Financial Statements and Discretionary Accruals (Meta-Analysis Study) - Narulita, Friska Dhea; Baderi, Rahmawati Nur; Hwihanus, Hwihanus (Journal of Advances in Accounting, Economics, and Management, 2024)
This article discusses the impact of fraud-on-fraud detection of financial statements and discretionary accruals through meta-analysis studies. Financial statement fraud is a serious problem that is increasingly prevalent in the global capital market, especially in developing countries such as China. This has driven the need for more sophisticated and effective detection methods. This study aims to identify factors that can affect the detection of financial statement fraud as well as the impact of fraud on the detection of financial statement fraud and discretionary accrual. This article also seeks to find better solutions in dealing with discretionary accruals that can affect investment decisions and public confidence in companies. The findings of the meta-analysis show that factors such as manipulation of accounting records, misrepresentation of information, and errors in the application of accounting principles can affect fraud detection. In addition, the impact of fraud on the detection of fraud in financial statements and discretionary accruals is also discussed comprehensively. This article suggests the need for more dynamic and responsive fraud detection methods to evolving risks.